2015
DOI: 10.1177/1059601115595935
|View full text |Cite
|
Sign up to set email alerts
|

When and Why Are Internal Job Transitions Successful? Transition Challenges, Hindrances, and Resources Influencing Motivation and Retention Through Basic Needs Satisfaction

Abstract: This study examines when and why internal job transitions enhance employees' motivation and retention. Building on the Challenge-Hindrance Framework and the Self-Determination Theory, we hypothesize that transition challenges (i.e., horizontal and vertical transition magnitude) satisfy people's basic psychological needs and may therefore enhance motivation and retention, whereas transition hindrances (i.e., increased work-life conflict) thwart basic needs satisfaction and are accordingly likely to decrease mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
(136 reference statements)
2
15
0
Order By: Relevance
“…Understood broadly as a function of factors such as career stage, control seeking, organizational mandate, and personal growth/novelty needs (e.g., Anderson, Milkovich, and Tsui 1981;Campion, Cheraskin, and Stevens 1994;Cron 1984;Feldman and Ng 2007;Nicholson 1984;Verbruggen, Cooman, and Vansteenkiste 2015).…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Understood broadly as a function of factors such as career stage, control seeking, organizational mandate, and personal growth/novelty needs (e.g., Anderson, Milkovich, and Tsui 1981;Campion, Cheraskin, and Stevens 1994;Cron 1984;Feldman and Ng 2007;Nicholson 1984;Verbruggen, Cooman, and Vansteenkiste 2015).…”
Section: Motivationmentioning
confidence: 99%
“…Nicholson and West (1989) discuss a process model in which employee transitions occur in four stages: (1) preparation (expectations and anticipation occurring before the change), (2) encounter (emotional impact and sense making occurring when first starting the new job), (3) adjustment (personal development occurring to better fit the requirements of the new job), and (4) stabilization (steadiness being achieved between the employee and the new role). Additional research has examined a variety of job transition aspects, including socialization (e.g., Batistič and Kaše 2015), employee retention (e.g., Verbruggen, Cooman, and Vansteenkiste 2015), and career development (e.g., Campion, Cheraskin, and Stevens 1994). Furthermore, firms can facilitate effective job transitions by providing training, mentoring, and social support to transitioners (Kraimer et al 2011;Moyle and Parkes 1999;Verbruggen, Cooman, and Vansteenkiste 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research based on SDT has revealed that individuals' experiences of having the needs for autonomy, relatedness and competence met at work leads to more positive views of potential workplace stressors (Van den Broeck, Ferris, Chang, & Rosen, 2016), and the satisfaction of psychological needs has similarly been conceptualised as psychological resources that assist individuals during difficult work periods (i.e., Verbruggen, De Cooman, & Vansteenkiste, 2015), in order to help buffer the detrimental effects of work stressors on well‐being (Viswesvaran, Sanchez, & Fisher, 1999). Alongside its effects on employee well‐being, psychological need satisfaction at work is linked with greater job engagement and less burnout (Van den Broeck et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance motivation big organizations with several levels of management may use internal transitions as an instrument for better motivation, but 'little is known about when and why internal transitions actually enhance employees' engagement and reduce their turnover intentions.' (Verbruggen, Cooman, & Vansteenkiste, 2015). The key idea for effective motivation may be in differentiating between transition challenges and transition hindrances for individuals inside organizations.…”
Section: Introductionmentioning
confidence: 99%